A novel hexahydroquinazolin-2-amine-based fluorescence sensor for Cu2+ from isolongifolanone and its biological applications. Issue 53 (30th June 2017) - Wang, Zhonglong; Yang, Jinlai; Yang, Yiqin; Fang, Hua; Xu, Xu; Rui, Jian; Su, Fan; Xu, Haijun; Wang, Shifa
Abstract : The isolongifolanone derivative (2c ) exhibit highly selective and sensitive fluorescence quenching towards copper ions, and this was used for real-time sensing of cooper ions in vivo . Abstract : Pyrimidine-based derivatives2a–2c were synthesized from renewable isolongifolanone, and compound2c exhibited high selectivity and sensitivity toward Cu 2+ ions with a low detection limit of 4 × 10 −8 M, a wide pH range (5–11), and a short response time (30 s). The sensor still retained good fluorescence selectivity to Cu 2+ ions when applied to fluorescence imaging in living black mice. Therefore, compound2c can be used as an effective fluorescence probe and imaging agent for detecting Cu 2+ ions.